2022
DOI: 10.3389/fpsyg.2022.853804
|View full text |Cite
|
Sign up to set email alerts
|

Neural Effects of Cognitive Behavioral Therapy in Psychiatric Disorders: A Systematic Review and Activation Likelihood Estimation Meta-Analysis

Abstract: BackgroundCognitive behavioral therapy (CBT) is a first-line psychotherapeutic treatment that has been recommended for psychiatric disorders. Prior neuroimaging studies have provided preliminary evidence suggesting that CBT can have an impact on the activity of brain regions and functional integration between regions. However, the results are far from conclusive. The present article aimed to detect characteristic changes in brain activation following CBT across psychiatric disorders.MethodWeb of Science, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…They noted that in this group, it can improve the emotion regulation by using effective and social intervention programs. The research of Yuan et al (2022) showed that CBT in patients with psychiatric disorders is associated with a significant decrease in activity in ECN, MPFC, ACC and Precuneus, and this decrease of activity can improve cognition and regulate activities. In addition, the findings of La Buissonniere-Ariza et al (2021) and Vuper et al (2021) show that CBT improves cognitive function by affecting internal connectivity and interaction between brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that in this group, it can improve the emotion regulation by using effective and social intervention programs. The research of Yuan et al (2022) showed that CBT in patients with psychiatric disorders is associated with a significant decrease in activity in ECN, MPFC, ACC and Precuneus, and this decrease of activity can improve cognition and regulate activities. In addition, the findings of La Buissonniere-Ariza et al (2021) and Vuper et al (2021) show that CBT improves cognitive function by affecting internal connectivity and interaction between brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the fact that these adjuvant techniques do not reproduce the dual model explaining CBT efficacy may contribute to the idea that CBT, as a set of therapeutic tools, activates different processes according to the specific tool used. This may also contribute to explaining the discrepancies observed in the neural bases of CBT efficacy [ 18 , 19 ]. These findings have at least two implications: (i) the design of treatment programs will be improved by translating these findings into clinical practice, and (ii) it is necessary to study each part of CBT packages, because they may activate different underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, data provided by neuroimaging studies about neural changes produced by CBT are more complex than the dual model [ 18 ]. A systematic review about the changes associated with CBT in mental health disorders has found a decrease in the activity of the default mode network [ 19 ]. This network includes the precuneus, posterior cingulate cortex, inferior lateral parietal gyrus, anterior cingulate cortex, and medial frontal cortex and is responsible for introspection processes, vigilance, and preparation for changes in the external environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBT may add extra value to the treatment process via different mechanisms. CBT modulates selective attention, executive functions, attributions, and learning and memory by strengthening the adaptive and flexible functioning of the prefrontal cortex [ 36 , 47 ]. Altogether, the antipsychotics plus CBT combination targets symptoms and cognitive biases focusing on two distinct levels: bottom-up reduction of abnormal salience to predictions (less conviction in beliefs) by antipsychotics and the enhancement of flexible top-down control from the prefrontal cortex (revision and updating of beliefs).…”
Section: Discussionmentioning
confidence: 99%